SPREAD IN FERGANA VALLEY AND USED STERILITY ILLNESSES SPICY HERBS’ BIOECOLIGICAL UNIQUENESS (Scientific journal of the Fergana State University, 2024)
The article contains information about medicinal plants used for infertility diseases growing in the Fergana Valley, as well as information about industrial plants. The main goal of the study is to study the bioecological properties of plants, as well as to reduce the number of infertility diseases through the correct use of plants given in the article. One of the main methods when examining plants is the observation method with which the morphology of plants is studied. A comparative method is used to determine more beneficial properties. The results of the study show the influence of phytohormones on the body of women and men. Phytohormones of the sage plant promote the growth of follicles and their maturation, raspberry leaves accelerate the growth process of the endometrial layer in the uterus. Pumpkin seeds contain oils that improve sperm quality. Wheat bran contains large amounts of zinc, which stimulates an increase in testosterone levels.Pistachio in men restores hormone levels, will help improve potency and prevent erectile dysfunction, in women it increases the production of the hormone progesterone. We can conclude that the plants of the Fergana Valley are very useful; infertility disease can be reduced by up to 5.6%